Left ventricular dysfunction and intra-ventricular dyssynchrony in idiopathic pulmonary arterial hypertension. (15th October 2022) - Jayasekera, G; Macdonald, A.; Mccomb, C.; Orchard, V.; Welsh, D.; Church, C.; Johnson, M.; Brewis, M.; Berry, C.; Radjenovic, A.; Peacock, A.
Abstract: Background: Left ventricular (LV) filling pressures are normal in idiopathic pulmonary arterial hypertension (IPAH). However, direct and indirect interactions between the RV and LV can affect LV performance. We explored LV strain and LV intra-ventricular dyssynchrony in IPAH using feature tracking CMR (CMR-FT). Methods: Seventy IPAH patients and 40 healthy volunteers were included. Patients underwent CMR and right heart catheterisation. The 4-chamber cine was used to calculate LV longitudinal strain (EllLV ). LV circumferential (EccLV ) and radial strain (ErrLV ) were derived from a short axis cine. LV longitudinal, circumferential and radial intra-ventricular dyssynchrony indices were calculated. Results: There were no differences between the IPAH and healthy volunteer group in LV ejection fraction (66.1% vs 64.2% p = 0.6672). EccLV (−29.1 vs −32.1 p = 0.0323) and EllLV (−16.6 vs −23.7 p < 0.0001) were lower in IPAH. In patients with more severe disease, there was greater impairment of ErrLV compared to mild disease (50.9 vs 87.5 P < 0.0001). LV synchrony was impaired in all directions in IPAH. ErrLV was associated with RV ejection fraction ( r = 0.66), RV end-systolic volume index ( r = −0.59), pulmonary vascular resistance (PVR)( r = 0.51) and stroke volume index (SVI)( r = 0.44). In a multivariate model with age, SVI and PVR, ErrLV (HR 0.970 p = 002) and radial dyssynchrony (HR 3.759 p < 0.0001) independently predicted survival. Conclusion: In IPAH, LV is dyssynchronous with impaired function. Measures of LV strain and intraventricular synchrony were associated with known markers of disease severity. These LV variables which are likely to be related to ventricular interaction, may add incremental value to known prognostic variables in IPAH. Highlights: IPAH is defined by normal LV filling pressures. IPAH patients had significant impairment in LV strain and intra-ventricular synchrony. These LV variables are likely to be related to ventricular interdependence. They may add incremental value to known CMR prognostic variables in IPAH.